Study of the effect of optical bleaching at selected photon energies on the optical absorption and thermoluminescence of LiF: Mg, Ti (TLD-100). (November 2017) - Reshes, G.; Druzhyna, S.; Biderman, S.; Eliyahu, I.; Oster, L.; Horowitz, Y.S.
Abstract: A new interpretation of the optical absorption energy spectrum of LiF:Mg, Ti (TLD-100) is presented in which the 4.0 eV band is composed of two-sub-bands at 3.84 eV and 4.3 eV. The new interpretation is of central importance in the understanding of the geminate recombination mechanisms giving rise to glow peak 4 and composite glow peak 5 in the thermoluminescence (TL) of TLD-100. Photon bleaches at energies of 3.6 eV and 4.2 eV on samples of gamma irradiated TLD-100 were carried out in order to investigate the correlation of the 4.3 eV absorption band with the electron-hole configuration giving rise to glow peak 5a and the 3.84 eV absorption band with the e-only configuration giving rise to glow peak 5. The increase in peak 4 (correlated with the hole-only configuration) induced by the 4.2 eV bleach is enhanced by 90% over the increase induced by the 3.6 eV bleach. The decrease in peaks 5a and 5 induced by the 4.2 eV bleach are enhanced by 400% and 50% respectively over the 3.6 eV bleach. The results are consistent with the suggested structures giving rise to the 4.3 eV and 3.84 eV bands observed in the optical absorption energy spectrum. Highlights: Effect of photon bleach on the TL glow curve of LiF:Mg, Ti. Evidence for spatially correlated TC/LC configurations in the OA spectrum. Correlation between TL glow peaks and OA bands in LiF:Mg, Ti.